Priest Alexander Ivantsov-Platonov and historians of Moscow University - Tsygankov Dmitrii (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The question of the uniﬁ ed ﬁeld of Church history studies in Russia’s pre-revolutionary era recently became under hot discussion among historians and theologians. Suggesting that the approved program of Church-historical research in this period has not been formed, experts are trying to ﬁnd the cause of this discrepancy between representatives of secular and ecclesiastical approach and facts about cooperation between them. The proposed publication shows the position of the Department of Church history at Moscow University at the end of 1894, when doctor of theology priest Alexander Ivantsov-Platonov decided to communicate his position to the secular historian and doctor of the universal history Mikhail Sergeyevich Corelin. For Ivantsov-Platonov it was a thought-out position. The Professor wanted to attract student attention and public interest to the problem of Church history. In this regard, in the absence of the nominee to vacancy from Theological Academy, Ivantsov-Platonov wanted to see on his chair secular historian, has already attracted the attention of students studying questions closely connected with the history of the Church. It was a risky option, because secular professors of the University were considered such an option primarily from the practical point of view, especially from the point of view of the curriculum of the faculty. Above all this project was not agreed by The Ministry of national education. This led to the failure of Ivantsov-Platonov project and ﬁnal marginalization of the Department of Church history at the historical-philological faculty of Moscow University in the early 20th century.